2009
DOI: 10.1016/j.str.2009.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Probing the “Dark Matter” of Protein Fold Space

Abstract: We used a protein structure prediction method to generate a variety of folds as alpha-carbon models with realistic secondary structures and good hydrophobic packing. The prediction method used only idealized constructs that are not based on known protein structures or fragments of them, producing an unbiased distribution. Model and native fold comparison used a topology-based method as superposition can only be relied on in similar structures. When all the models were compared to a nonredundant set of all know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
109
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 24 publications
1
109
0
Order By: Relevance
“…Third, many of the lowest-energy 2D HP structures are highly compact but not maximally compact, as for real globular proteins [158,299], and a significant fraction of compact structures are not encodable by any HP sequence as its unique native structure [158,162]. The latter observation may bear on the question of whether the currently known set of globular protein folds is nearly complete in its coverage of all physically possible compact folds, as discussed in §3.1 [286][287][288][289][290], but one has to also keep in mind that the HP model interaction potential is less heterogeneous, and thus entails fewer encodable structures, than model potentials that contain repulsive interactions or otherwise more heterogeneous interactions [158,322,323]. Fourth, the 2D HP lattice model provides sequences that act like evolutionary bridges [161, 178,204,239,299] (see §3.5), encode for autonomous folding units [292,316,324], and exhibit homology-like behaviours [295], all similar to properties observed in real proteins.…”
Section: Model Interactions and Their Biophysical Basismentioning
confidence: 99%
“…Third, many of the lowest-energy 2D HP structures are highly compact but not maximally compact, as for real globular proteins [158,299], and a significant fraction of compact structures are not encodable by any HP sequence as its unique native structure [158,162]. The latter observation may bear on the question of whether the currently known set of globular protein folds is nearly complete in its coverage of all physically possible compact folds, as discussed in §3.1 [286][287][288][289][290], but one has to also keep in mind that the HP model interaction potential is less heterogeneous, and thus entails fewer encodable structures, than model potentials that contain repulsive interactions or otherwise more heterogeneous interactions [158,322,323]. Fourth, the 2D HP lattice model provides sequences that act like evolutionary bridges [161, 178,204,239,299] (see §3.5), encode for autonomous folding units [292,316,324], and exhibit homology-like behaviours [295], all similar to properties observed in real proteins.…”
Section: Model Interactions and Their Biophysical Basismentioning
confidence: 99%
“…4B and Fig. S8) with high occurrence of disulfide bonds is a signature, suggesting that many dark proteins are newly evolved folds (35) exploring the dark matter of protein folding space (12).…”
Section: Resultsmentioning
confidence: 99%
“…The analogy to dark matter has inspired surveys of other "unknown" properties of proteins; for example, Levitt (6) examined "orphan" protein sequences that do not match to known sequence profiles, which he termed the "dark matter of the protein universe," and Taylor et al (12) investigated the "dark matter of protein fold space" (i.e., theoretically plausible folds that have not been observed in native proteins). The same analogy has been used in studies of so-called "junk DNA" (13), which revealed a "hidden layer" of noncoding RNAs (14).…”
mentioning
confidence: 99%
“…The virosphere structure space may contain structurally stable but evolutionary not-yet-observed protein folds, also called the 'dark matter' of protein structure space [68]. There is ....Pr ospects & Overviews A. Abroi and J. Gough a discrete-continuous duality of protein structure space (recently reviewed by Grishin and coworkers [69]), which is based on knowledge that the space is largely discrete in the evolutionary sense, but continuous geometrically.…”
Section: The Evolutionary History Of Viral Protein Domains Can Be Elumentioning
confidence: 99%